Jewelry and Art of Vlakno Cave (Archaeologia Adriatica, 2009)
The Vlakno cave is situated in the central part of the island of Dugi Otok between settlements Luka and Savar. The cave was suitable for dwelling of a smaller group throughout the year due to its look, size and orientation. The third campaign of the archaeological research was undertaken at the beginning of 2010 with the aim of determining complete startigraphy of the site so that the excavation was conducted within previously opened Trench B (fig. 1).In the previous campaigns the level of tephra, Neapolitan Yellow Tuff was reached. Analyses indicate that this layer was formed 14 500 years ago. In the new campaign additional 80 cm of deposits under tephra have been excavated, and the bottom of the cave was not reached until the end of the campaign. Under the tephra there are three main layers separated with two thin interlayers of ash and burnt soil which actually represent walking surfaces from the period when the cave was in use. Preliminary analyses of the material from all three layers indicate to the Epigravettian period corresponding with the general development of the Upper Palaeolithic on both sides of the Adriatic. Dates acquired for layers under tephra indicate age from 12. 710 to 12. 120 cal. years BC (14. 660 to 14. 060 cal. years BP). At the beginning of the new excavation decrease of the remains of marine organisms was evident, and the remains of big terrestrial animals refer mostly to big ruminants. There are less flint tools, although they are still represented with a significant number of specimens. There are also bone tools, such as perforated teeth of a deer (Cervus elaphus), perforated shells and snails (Cyclope neritea, Columbella rustica and shells of the genus Glycimeris). Eight perforated deers' teeth were found, six different perforated shells and a bead made of a shell of the genus Entalina (Dentalium tetragonum) (fig. 2). Alongside these finds, we need to mention fragments of ten bone awls and punches.Besides jewelry, meaning of the aesthetics gains even more importance regarding the find of two fragments of chert nodules in the same layer. One of them is decorated with a row of short, parallel and two horizontal incisions on the cortex (fig. 5). This was a segment of a larger depiction, continuing in three directions in relation to the extant segment. Unfortunately other fragments are missing which is why it is impossible to discuss the type of depiction. Nodule is broken, only its segment is preserved. It is triangular in cross-section, 3,6 cm long. Preliminary analyses indicate that it was exposed to heating before it was broken.Another fragment of a nodule was found in the same layer, semicircular in cross-section. Incisions in the cortex are shallow, filling the entire surface as opposed to the previously mentioned fragment. This is a row of slanted parallel short incisions encircling the flake (fig. 6).Meaning of these objects remains unknown until the time of possible discovery of some other fragment. There are no indications of functional characteristics of these incisions which is why it is reasonable to suppose that their purpose was of aesthetic nature to say the least. It is possible that depictions on the stone from Vlakno have far more complex meaning. Archaeologists assume that some of the art of the Upper Palaeolithic was used for information storage. Geometric forms might represent different marks or symbols, messages illegible to a modern man.These are not the only decorated objects from Vlakno. On a bone awl is a row of horizontal, short incisions on the proximal part which were not created as a result of working or using bone (cutmarks) but they undoubtedly represent a decoration of the object. Similar incisions (four short incisions) were found on the distal part of the bone punch. These incisions can only have aesthetic meaning as well as on the previously mentioned example. However they may be a sign of ownership or affiliation to a group, or, since the incisions repeat, they may represent a system of numbers.
Keywords: Dugi otok; Vlakno cave; Palaeolithic; Epigravettian; Chert nodule with incisions; jewelry